Veterinary nursing in the United Kingdom: Identifying the factors that influence retention within the profession - Jeffery, Andrea; Taylor, Eleanor (Frontiers in Veterinary Science, 2022)
The UK regulatory body for registered veterinary nurses (RVNs), the Royal College of Veterinary Surgeons (RCVS), maintains the professional register of RVNs. Every year, a proportion fail to re-join the register. This research aimed to identify the factors that predict retention and to make recommendations to inform the Royal College of Veterinary Surgeons as the regulator as well as both the veterinary nursing and veterinary professions. An analysis of the raw quantitative data generated by the 2014 and 2019 RCVS surveys of the veterinary nurse profession was undertaken using multivariable logistic regression analysis. First, bivariable associations were estimated using unadjusted odds ratios to explore whether there are any (unconditional) associations between each predictor and the outcome. Predictors that were significant unconditional predictors of intention to leave were then entered into a multivariable logistic regression, yielding adjusted odds ratios. Quantitative analysis found significant relationships between intention to leave and the following factors in both the 2014 and 2019 survey data: job satisfaction; believing that veterinary nursing offers good opportunities for career progression; satisfaction with employer support; and having a second job. The following factors were significant in 2014, but not in 2019: undertaking nurse clinics, feeling valued, and being respected by veterinary surgeons. The factors that influence the retention of registered veterinary nurses (RVNs) within the profession are multifactorial and individual. Nurses are responsible for ensuring that those they work with are aware of their skill set and that they themselves are accountable for utilisation of those skills. When veterinary nurses are supported by their employers, they are more likely to stay in the profession. Having a clearly defined career structure and mapped routes for progression will be helpful with retention. A sense of job satisfaction was another important factor in retention. A pay structure linked to a career pathway framework, such as in human-centred nursing, is an area for further work.